2016
DOI: 10.1016/j.jcm.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Demographic Analysis of Patients Seeking Care at a Free University Chiropractic Clinic

Abstract: This study found that new patients seeking care at a free student chiropractic clinic within a university health center in the Buffalo area mainly consisted of young single adults, with chronic lumbar spine complaints with few comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…19 Studies from teaching institutes in Mexico, Missouri, and New York have also found similar results when studying all age groups, with the most common chief complaint being low back pain. 15,17,18 The current study reported 45% of older patients had lower back pain as their chief complaint. In the 2005 study, the most common complaint was also low back pain at 38.1% for all age groups.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…19 Studies from teaching institutes in Mexico, Missouri, and New York have also found similar results when studying all age groups, with the most common chief complaint being low back pain. 15,17,18 The current study reported 45% of older patients had lower back pain as their chief complaint. In the 2005 study, the most common complaint was also low back pain at 38.1% for all age groups.…”
Section: Discussionmentioning
confidence: 55%
“…19 The second most common chief complaint of the current study was neck pain at 21%, which was a similar result (23%) to a study conducted at a chiropractic teaching college in the United States. 18 Interestingly, the second most common chief complaint in US 13 and Mexican 15 studies were extremity complaints at 29.5% and 28%, respectively. Extremity complaints in the current study were reported by 8% compared with the previous NZCC study that reported extremity complaints by 5.8%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The slightly higher percentage of women (52%) seeking chiropractic care has been described previously, whereas our patient population with the most common age group of 40–49 years (21.4%), followed by 50–59 years (20.9%), seems to be older compared to other chiropractic settings [ 24 ]. The most common main diagnosis of low back pain, followed by neck pain, is consistent internationally [ 24 ] and in other chiropractic teaching clinics [ 25 27 ]. Patients averaged 7 chiropractic visits during their episode of care, with 83% having 11 visits or less.…”
Section: Discussionmentioning
confidence: 85%
“…18 The most common main diagnosis of low back pain, followed by neck pain, is consistent internationally 18 and in other chiropractic teaching clinics. [19][20][21] Patients averaged 7 chiropractic visits during their episode of care, with 83% having 11 visits or less. While 95% of chiropractic teaching institutions report the routine use of PROMs for low back pain patients, 22 evidence about the current use of PROMs among chiropractors in routine clinical practices is limited.…”
Section: Discussionmentioning
confidence: 99%